Effect of Glyburide vs Subcutaneous Insulin on Perinatal Complications Among Women With Gestational Diabetes: A Randomized Clinical Trial. Issue 9 (September 2018) - Sénat, Marie-Victoire; Affres, Helene; Letourneau, Alexandra; Coustols-Valat, Magali; Cazaubiel, Marie; Legardeur, Helene; Jacquier, Julie Fort; Bourcigaux, Nathalie; Simon, Emmanuel; Rod, Anne; Héron, Isabelle; Castera, Virginie; et al.
Abstract : (Abstracted from JAMA 2018;319(17):1773–1780) Gestational diabetes continues to increase nationally and globally. The American Diabetes Association currently recommends insulin, the only Food and Drug Administration–approved pharmacologic agent, as first-line treatment for women with gestational diabetes mellitus requiring medications.